VALLEY BOTTOM CLAY DISTRIBUTION AND ADAPTED DRAINAGE TECHNIQUES - Amadou Keïta; Laszlo G. Hayde; Hamma Yacouba; Bart Schultz (International Association of Lowland Technology, 2014)
Waterlogged valley bottom soils of Tropical Savannah are areas where the richest traditional cropping systems are found, but they also face adverse physico-chemical conditions which can drastically drop rice yield. Subsurface drainage has been used for many areas to alleviate waterlogging. However, this drainage is dependent on clay distribution, type and location. The current paper analyses these factors for the case of Tiefora, a 16 ha valley bottom irrigated rice scheme in Burkina Faso. For this purpose, nine boreholes, with depths from 2 to 6 m, were realised. A total of 51 samples of soils were extracted at various depths, based on soil changes in texture and colour. These samples underwent grain-size-analysis. A comparative non-linear regression was performed on the clay distribution. Quadratic regression was the most appropriate. In addition, clay proportions were high - 20-30% in the 2 m topsoil - in the upstream and middle areas. A more important - 30-40% - peak was reached in the downstream area at 1 m, with a much smaller thickness (less than 50 cm) and higher permeability. These results suggest the application of mole drainage in the valley, except downstream where the classical Hooghoudt pipe subsurface drainage can be implemented.